Universal Health Coverage and the Right to Health: From Legal Principle to Post-2015 Indicators. (July 2015) - Sridhar, Devi; McKee, Martin; Ooms, Gorik; Beiersmann, Claudia; Friedman, Eric; Gouda, Hebe; Hill, Peter; Jahn, Albrecht
Universal Health Coverage (UHC) is widely considered one of the key components for the post-2015 health goal. The idea of UHC is rooted in the right to health, set out in the International Covenant on Economic, Social, and Cultural Rights. Based on the Covenant and the General Comment of the Committee on Economic, Social, and Cultural Rights, which is responsible for interpreting and monitoring the Covenant, we identify 6 key legal principles that should underpin UHC based on the right to health: minimum core obligation, progressive realization, cost-effectiveness, shared responsibility, participatory decision making, and prioritizing vulnerable or marginalized groups. Yet, although these principles are widely accepted, they are criticized for not being specific enough to operationalize as post-2015 indicators for reaching the target of UHC. In this article, we propose measurable and achievable indicators for UHC based on the right to health that can be used to inform the ongoing negotiations on Sustainable Development Goals. However, we identify 3 major challenges that face any exercise in setting indicators post-2015: data availability as an essential criterion, the universality of targets, and the adaptation of global goals to local populations.